The Detection of Carbapenem-Resistant Gram-Negative Bacilli (WHO Priority Pathogens) in Blood Cultures from Basrah Hospitals, Iraq : WHO Priority Pathogens in Basrah Hospitals - Thanoon, Noor; Mohammed, Khairallah AS (Scientific Journal of Medical Research, 2025)
Objective: To investigate the prevalence and characteristics of carbapenem-resistant Gram-negative bacilli, classified as WHO Priority Pathogens, isolated from blood cultures in major hospitals across Basra Province, Iraq, over the past four years. Methods: Blood samples were processed using BacT/Alert systems, with bacterial identification and antimicrobial susceptibility testing performed via the VITEK® 2 system. Results: Among the 289 Gram-negative bacterial isolates identified in this study, 270 (93.4%) were categorized as WHO priority pathogens. Among these, Escherichia coli was the most prevalent species, accounting for 103 isolates (38.14%), followed by Klebsiella pneumoniae with 69 isolates (25.56%). Pseudomonas aeruginosa and Acinetobacter baumannii were also notable, with 37 (13.7%) and 27 (10%) isolates, respectively. E. coli showed significant resistance to ceftazidime (53.9%), cefuroxime (44.7%), aztreonam (51.4%), and colistin (3.4%). K. pneumoniae also exhibited high resistance to cephalosporins and aztreonam, while P. aeruginosa showed substantial resistance to multiple agents, including imipenem (35%) and colistin (18%). A. baumannii was highly resistant to most tested antibiotics, including imipenem (48%) and meropenem (45%), with moderate resistance to colistin (7%). Conclusion: These findings reflect global resistance trends and underscore the urgent need for robust AMR surveillance, antibiotic stewardship, and alternative therapies to address the growing challenge of MDR and XDR infections in healthcare settings.